Analysis and Implementation of the ISSAF Framework on OSSTMM on Website Security Vulnerabilities Testing in Polinema - Muhammad Alif Nabila; Putri Elfa Mas'udia; Rachmad Saptono (Politeknik Negeri Malang, 2023)
Along with the increasing number of websites circulating on the Internet, the security holes that arise are also increasing. The Electrical Engineering Department's website is no exception, especially on the Electrical Engineering Department's website which has never been audited to scan for security holes on the Electrical Engineering Department's website so the level of reliability of the Electrical Engineering Department's website cannot be known. On this basis, a study entitled